2008
DOI: 10.1002/ldr.855
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of prescribed burning, chopping and clearing on runoff, infiltration and erosion in a shrubland area in Galicia (NW Spain)

Abstract: The immediate effects of three different fuel management treatments on runoff, infiltration and erosion were evaluated in a mixed heathland in Galicia (NW Spain). The treatments compared were: prescribed burning, shrub chopping and shrub clearing.Rainfall simulations were conducted immediately before and after fuel reduction treatments. A rainfall rate of 67 mm h À1 was applied for 30 min to each runoff plot.Application of treatments significantly affected runoff and infiltration, but the parameter most affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…The average fuel load in the area was 2.7 ± 0.5 kg m −2 . Fuel loads determined in heathlands ranged between 1.8 kg m −2 (SW Spain, Zavala et al, 2009) and 2.0 kg m −2 (in Galicia, NW Spain; Fernández et al, 2008). Small variations were observed in the severity and intensity of fire across the burnt area.…”
Section: Experimental Burningmentioning
confidence: 97%
“…The average fuel load in the area was 2.7 ± 0.5 kg m −2 . Fuel loads determined in heathlands ranged between 1.8 kg m −2 (SW Spain, Zavala et al, 2009) and 2.0 kg m −2 (in Galicia, NW Spain; Fernández et al, 2008). Small variations were observed in the severity and intensity of fire across the burnt area.…”
Section: Experimental Burningmentioning
confidence: 97%
“…3). In three of these cases (Fernández et al, 2006(Fernández et al, , 2008(Fernández et al, , 2012, the authors of the publications provided this information, upon a specific request. In the remaining four cases (Dobrowolsky et al, 1992;Emmerich-Cox, 1994;Johansen et al, 2001b;Knight et al, 1983), the present authors felt confident to estimate soil burn severity following the classification by Vega et al (2013a), based on the description of the fire and of post-fire conditions in the article.…”
Section: Data Compilation Revision and Gap-fillingmentioning
confidence: 99%
“…Field rainfall simulations experiments (RSE's) have been widely used to study the effects of fire on runoff and sediment losses (e.g., Emmerich and Cox, 1992;Robichaud, 2000;De Luis et al, 2003;Ferreira et al, 2005;Fernández et al, 2008;Groen and Woods, 2008). Nevertheless, the most comprehensive recent reviews on post-fire erosion Shakesby, 2011;Moody et al, 2013) have not included these RSE studies.…”
Section: Introductionmentioning
confidence: 98%
“…Drastic mortality rates in the early recovery years can be caused by a combination of factors, including competition, herbivory, and the insufficient root development to handle summer drought conditions. Seed bank loss can largely be attributed to erosion (Keeley 1977) and coincidence of bare soil and heavy rain may increase erosion (Fernández et al 2008;Gill and Groves 1981). Fernandez et al (2008) reported that fuel treatments affected the initial runoff, infiltration, and erosion in a gorse shrubland community in northwest Spain, especially after prescribed burning compared to mastication.…”
Section: Treatment Typementioning
confidence: 99%